Batik Motif Saik Galamai Dalam Busana Kontemporer - Siti Fatihul; Desi Trisnawati (VisArt: Jurnal Seni Rupa dan Design, 2025)
“Saik Galamai Motif Batik in Contemporary Fashion”, aims to create contemporary fashion using saik galamai motif batik. Galamai is a typical Minang food that is cut into a rhombus shape which has the meaning of caution of the Minang people in doing, behaving and in facing something. Contemporary fashion is clothing that reflects contemporary styles and trends with the ability to combine traditional fabrics with modern styles. The creation of this work uses an exotic dramatic style with a simple fashion style that can be seen in the form of clothing that is not excessively packaged in a unique and contemporary fashion trend with current trends. The creation of this work creates contemporary clothing using saik galamai motif batik. In addition, it also provides updates to existing clothing, the artist uses brown and cream materials as the main colors. With maxmara and tulle materials using saik galamai motif batik. Realizing clothing with sewing techniques, sequin embroidery techniques and corsage decoration techniques. This fashion creation embodies deluxe ready-to-wear clothing. The deluxe ready-to-wear clothing uses sequin embroidery and corsage techniques, while the haute couture clothing uses sequin embroidery and corsage techniques